Edukasi Pembebasan Pasung Pada Keluarga Dengan Gangguan Jiwa - Rasmawati; A. Nur Anna AS; Wahyuni; Indargairi; Kamaluddin Palinrungi; Muh. Hamka; Jumriani; Nur Chairul (Jurnal Pengabdian Pada Masyarakat, 2022)
EDUCATION FOR THE RELEASE OF PASUNG IN FAMILIES WITH MENTAL ILLNESS. Pasung is a restraint for people with mental illness (PWMI) who have not all been handled. The incidence of pasung in severe mental illness shows that 14% have been pasung and 31.5% have been pasung in the last 3 months. Based on interviews with community health center nurses and PMWI’s families, They were said that PWMI had been pasung for 3 years to tens of years. The nurses have tried to provide education to the family but have not succeeded because the family is afraid that PWMI will run away and injure themselves and others. Therefore, the community health center nurses collaborate with the Hospital and Health Colleges in handling pasung. The purpose of this community service is to provide education to the families of PWMIs in the form of releasing PWMIs, treating PWMIs at the hospital, and PWMI's care after pasung. This community service was carried out in Jeneponto Regency on September 18-23, 2020. The method in this community service was providing education and mediation to families. The results of this community service were education and mediation have been carried out for 4 PWMI’s families. Of the 4 families, 3 of them are willing to let go of their pasung and get treatment at the hospital. Community service is important because through this activity, families can be well literate so that the burden on the family is reduced and PWMI has the opportunity to be productive.